Jurnal Penjaminan Mutu Corpus Thematic Analysis : Trends In Quality And Quality Assurance Research - Barrameda, Caridad Nacion; Sudarsana, I Ketut; Galang, Aljon Delmo; Ancho, Inero Valbuena (Jurnal Penjaminan Mutu, 2020)
Research as a component of quality assurance serves as a venue to provide spaces for scholarly dialog among experts in bridging together aspects and elements that call for inquiry and debate. This study employs documentary analysis to effectively address the need of the research. Articles accepted and published in the Journal of Quality Assurance are downloaded, revisited, and analysed. Based on available online data, this study includes articles published from year 2018, covering publication issues after it was included in the list of the Asean Citation Index (ACI). In-depth scrutiny of data revealed three main arguments pertaining to inquiries of articles accepted and published in the journal: Quality Assurance in Education in Bountiful Quantity, From the Inner Psyche to the Social Systems of Humankind, and The Roles of Employers and Employees. The thrust of the journal in championing research works related to ‘quality assurance’ has been instrumental in contextualizing the concept of quality as applied in diverse fields of studies. The journal has served as a niche for scholars in advocating a community of practice where knowledge production is evident and scholarly approaches to research inquiries are manifested.